Inhibition of Gluconeogenesis in Primary Hepatocytes by Stromal Cell-derived Factor-1 (SDF-1) through a c-Src/Akt-dependent Signaling Pathway - Liu, Hui-Yu (American Society for Biochemistry and Molecular Biology, 2008)
Hepatic gluconeogenesis is elevated in diabetes and a major contributor to hyperglycemia. Stromal cell-derived factor-1 (SDF-1) is a chemokine and an activator of Akt. In this study, we tested the hypothesis that SDF-1 suppresses hepatic gluconeogenesis through Akt. Our results from isolated primary hepatocytes show that SDF-1α and SDF-1β inhibited glucose production via gluconeogenesis and reduced transcript levels of key gluconeogenic genes glucose-6-phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK). Additionally, SDF-1α and SDF-1β both inhibited activation of the PEPCK promoter. In examining the mechanism by which SDF-1 inhibits gluconeogenesis, we found that SDF-1 promoted phosphorylation of Akt, FoxO1, and c-Src, but did not activate insulin receptor substrate-1-like insulin. Blockade of Akt activation by LY294002, FoxO1 translocation by constitutively nuclear FoxO1 mutant, or c-Src activation by the chemical inhibitor PP2, respectively, blunted SDF-1 suppression of gluconeogenesis. Finally, our results show that knocking down the level of SDF-1 receptor CXCR4 mRNA blocked SDF-1 suppression of gluconeogenesis. Together, our results demonstrate that SDF-1 is capable of inhibiting gluconeogenesis in primary hepatocytes through a signaling pathway distinct from the insulin signaling.